Tree Species Composition and Natural Regeneration Status of Southeast Region of Bangladesh - Abir Dey; Aklima Akther (Universitas Gadjah Mada, 2020)
The study aimed to quantify and discuss the current condition of the tree species composition and natural regeneration of southeast parts of Bangladesh (Cox’s Bazar North Forest Division). A total of 121 stems having dbh ≥10cm and 3481 stems of regenerating tree species (dbh <10cm) per hectare were recorded. A large trees comprised of 17 species belonging to 10 families and 14 genera and 30 regenerating tree species belonging to 19 families and 27 genera have been found. The forests were highly non-uniform, with three or four species represented most of the stands. The values of diversity indices indicated limited plant diversity, which is dominated by two or three tree species. Stems of 10-30 cm dbh contributed almost 90% of the total stem density, whereas more than 80% of the total basal area still belonged to trees with dbh 100 cm or above. Dipterocarpus turbinatus was the most dominant species which have the highest Importance Value Index (IVI) with 135.82 and embodied 37.71% of the total stand density and 72.19% of total basal area. The study will provide scientific basis for the future implementation of forest conservation strategies in tropical forests of Southeast Asia, particularly in Bangladesh. This study may also pave the way to further research on regeneration potentials of the native species for conservation and enhancement of forests in future.